Engineering the N-glycosylation pathway of Nicotiana tabacum for molecular pharming using CRISPR/Cas9 - Göritzer, Kathrin; Grandits, Melanie; Grünwald-Gruber, Clemens; Figl, Rudolf; Mercx, Sébastien; Navarre, Catherine; Ma, Julian K-C.; Teh, Audrey Y-H. (Frontiers in Plant Science, 2022)
Molecular pharming in plants offers exciting possibilities to address global access to modern biologics. However, differences in the N-glycosylation pathway, including the presence of β(1,2)-xylose and core α(1,3)-fucose can affect activity, potency and immunogenicity of plant-derived proteins. Successful glycoengineering approaches towards human-like structures with no changes in plant phenotype, growth, or recombinant protein expression levels have been reported for Arabidopsis thaliana and Nicotiana benthamiana. Such engineering of N-glycosylation would also be desirable for Nicotiana tabacum, which remains the crop of choice for recombinant protein pharmaceuticals required at massive scale and for manufacturing technology transfer to less developed countries. Here, we generated N. tabacum cv. SR-1 β(1,2)-xylosyltransferase (XylT) and α(1,3)-fucosyltransferase (FucT) knockout lines using CRISPR/Cas9 multiplex genome editing, targeting three conserved regions of the four FucT and two XylT genes. These two enzymes are responsible for generating non-human N-glycan structures. We confirmed full functional knockout of transformants by immunoblotting of total soluble protein by antibodies recognizing β(1,2)-xylose and core α(1,3)-fucose, mass spectrometry analysis of recombinantly produced VRC01, a broadly neutralizing anti-HIV-1 hIgG1 antibody, and Sanger sequencing of targeted regions of the putative transformants. These data represent an important step towards establishing Nicotiana tabacum as a biologics platform for Global Health.